Omotic lexicon in its Afro-Asiatic setting VI: Addenda to Omotic roots with *ḅ-, *ṗ-, *p- (or *f-) - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper is a new contribution to revealing the Afro-Asiatic heritage in the lexicon of the Omotic languages by means of interbranch comparison using a.o. the ancient Egypto-Semitic evidence.